Triage of Septic Patients Using qSOFA Criteria at the SAMU Regulation: A Retrospective Analysis. (2nd January 2018) - Jouffroy, R.; Saade, A.; Carpentier, A.; Ellouze, S.; Philippe, P.; Idialisoa, R.; Carli, P.; Vivien, B.
Abstract: Purpose : One of the major prognostic factors in the management of sepsis is the early initiation of appropriate treatment. To serve this purpose, early identification and triage of patients are crucial steps, which are still not optimal. The objective of this study was to determine whether the quick Sequential (Sepsis-related) Organ Failure Assessment (qSOFA) score is an accurate method for prehospital triaging of septic patients. We evaluated whether the use of qSOFA criteria collected by the Service Mobile d'Urgence et de Réanimation 15 (SAMU 15) regulation call center during prehospital care would facilitate appropriate intensive care unit (ICU) admission of patients with septic syndromes.Methods : We conducted a retrospective observational register-based study using data collected between April 01 and May 31 2011. These data are based on call registry reports of calls received by the Paris Emergency regulation call centre during prehospital management of patients. All patients with suspected infection were included in the study and evaluated using qSOFA and systemic inflammatory response syndrome (SIRS) criteria. The primary outcome was Intensive Care Unit (ICU) admission.Results : Among the 30 642 reports received, 141 patients with presumed sepsis were included. Twenty-two patients were admitted to an ICU. The qSOFA and SIRS scores were the same in predicting admission to an ICU (p = 0.26). The qSOFA had a sensitivity of 75% and a specificity of 68% for ICU admission whereas the SIRS had a sensitivity of 87% and a specificity of 43%. At day 28, 12 patients (9%) had died, 5 of them in the ICU. The negative predictive value reached 93% and 94% for pre-hospital qSOFA and SIRS respectively. Pre-hospital systolic blood pressure (SBP) ≤100 mmHg was significantly associated with ICU admission (OR = 4.19 [1.89–9.84]), while all other criteria were not.Conclusion : The current study reports no difference between the SIRS and the qSOFA scores for prehospital triage of septic patients to predict ICU admission. Both scores have comparable, pertinent, negative predictive value for ICU admission. Nevertheless, an improved score for pre-hospital triaging is needed to predict ICU admission of septic patients.